637 Ergonomic risk factors, musculoskeletal symptoms, exertion and workload among physiotherapists in a single rehabilitation centre. (24th April 2018) - Rajkumar, Joshua Samuel; Sharan, Deepak
Abstract : Introduction: Physiotherapists (PTs) apply manual forces such a pushing, pulling and lifting, maintain hazardous postures and static loading during treatment, which predisposes them to work related musculoskeletal disorders (WRMSD). Hence, the aim of this study was to evaluate the risk factors for WRMSDs in a group of PTs working in a rehabilitation centre. Methods: A prospective study was conducted among 120 PTs working in a neuromusculoskeletal rehabilitation centre in an Industrially Developing Country. Musculoskeletal and neurological conditions in adult and paediatric populations were primarily treated in the centre. The PT's were evaluated with a self-reported questionnaire which included demographic data, short-form Work Style Questionnaire, Nordic Musculoskeletal Pain Questionnaire, Borg CR 10 and NASA Task Load Index. The inclusion criteria were: PTs working for a minimum of 6 months of experience in the same centre, treating a minimum of 6 hours per day and had availed no more than 15 days of leave in the last 6 months. Result: The mean age of the PTs was 29.5 years. On an average, the PTs worked for 8±1.2 hours per day for 6 days a week. 78% of the PTs complained of pain or discomfort within the past 6 months. The commonest sites of pain were lower back (58%), neck (52%), upper back (50%), wrist and hand (35%), shoulder (32%) and ankle (10%). Analysis of short form of workstyle questionnaire revealed that 70% of the subjects reported an adverse workstyle risk (total score >28). The perceived exertion and workload were also high as over 75% of the PTs had scores of >15 (Borg CR 10) and >50 (NASA Task Load Index) respectively. Discussion: PTs handling both adult and paediatric patients had high risk of developing WRMSD and appropriate recommendations were given based on the results to ensure prevention of WRMSD.